Pharmacological Treatment of Primary Chronic Osteomyelitis: A Case Report - Oliveira, Jhosepher Previati de; Migliolo, Rodrigo Chenu; Lemos, José Benedito Dias; Gouveia, Márcia Maria de (Journal of Oral Diagnosis, 2023)
Paracoccidioidomycosis (PCM) is an infection caused by the dimorphic fungus Paracoccidioides brasiliensis, which has a predilection for hot and humid places; thus, this disease has a particularly high incidence in Brazil. Children, adolescents, and adults can be affected by acute/subacute or chronic PCM. To describe the clinical-pathological characteristics and treatment of a case of chronic PCM oral lesion. The oral examination of a 57-year-old male patient revealed moriform stomatitis on the perioral region (irregular shape), lips vermilion, and continuity with the jugal mucosa. After an incisional biopsy, the anatomopathological analysis confirmed the diagnosis of PCM. The patient was referred to a reference center for tropical diseases and treated with 400mg sulfamethoxazole and 80mg trimethoprim twice a day. Since some adverse effects were observed, the treatment was switched to 100mg of itraconazole twice a day. The follow-up examination revealed accelerated healing of the oral lesions and reduction of the inflammatory process. Stomatologists play a key role in the identification of PCM oral lesions and referral for adequate treatment by an infectious disease specialist.